Production of Complex Amylase Enzymes From Aspergillus Awamori KT-11. Its Application To Hydrolyze Cassava and Taro Starch - Ruth Melliawati; Nuryati Nuryati (UNIVERSITAS NEGERI PADANG, 2019)
Indonesia as an agricultural country rich in various types of plants including tubers. The purpose of this study was to produce and apply complex amylase enzymes from Aspergillus awamori KT-11 in hydrolyzing cassava and taro starch to liquid sugar. The production of complex amylase enzymes is carried out in a liquid and solid medium. The hydrolysis of starch into sugar is carried out with several enzyme concentrations (2-10%) and starch concentrations (5-25%) at room temperature (30ºC) and 60⁰C for 3 hours, 24 hours - 72 hours. TLC tests were carried out on sugar from hydrolysis of cassava starch and taro flour to determine the type of sugar formed.As a result, the highest enzyme activity was obtained in the solid medium formation (242.83 Units/ml). The best condition for hydrolyzing starch is 15% starch concentration, 10% enzyme concentration at 60ºC for 72 hours. The results of hydrolysis sugar were 9.52 mg / ml (taro) and 9.37 mg/ml (cassava) respectively, with an incubation time of 72 hours.The TLC analysis showed that sugar Rf from cassava was detected as lactose and Rf from Talas flour as maltose.